The Cretaceous Ofuku Pluton and Its Relation to Mineralization in the Western Akiyoshi Plateau, Yamaguchi Prefecture, Japan. Issue 2 (28th March 2016) - Sasaki, Yuka; Imaoka, Teruyoshi; Nagashima, Mariko; Nakashima, Kazuo; Sonehara, Takafumi; Yagi, Koshi; Itaya, Tetsumaru
Abstract: The relationship between the magmatism of the Cretaceous Ofuku pluton and mineralization in and around the Akiyoshi Plateau, Yamaguchi Prefecture, Japan was investigated using a combination of field observation, petrographic and geochemical analyses, K–Ar geochronology, and fluid inclusion data. The Ofuku pluton has a surface area of 1.5 × 1.0 km, and was intruded into the Paleozoic accretionary complexes of the Akiyoshi Limestone, Ota Group and Tsunemori Formation in the western part of the Akiyoshi Plateau. The pluton belongs to the ilmenite‐series and is zoned, consisting mainly of early tonalite and granodiorite that share a gradational contact, and later granite and aplite that intruded the tonalite and granodiorite. Harker diagrams show that the Ofuku pluton has intermediate to silicic compositions ranging from 60.4 to 77.9 wt.% SiO2, but a compositional gap exists between 70.5 to 73.4 wt.% SiO2 (anhydrous basis). Modal and chemical variations indicate that the assumed parental magma is tonalitic. Quantitative models of fractional crystallization based on mass balance calculations and the Rayleigh fractionation model using major and trace element data for all crystalline phases indicate that magmatic fractionation was controlled mainly by crystal fractionation of plagioclase, hornblende, clinopyroxene and orthopyroxene at the early stage, and quartz, plagioclase, biotite, hornblende, apatite, ilmenite and zircon at the later stage. The residual melt extracted from the granodiorite mush was subsequently intruded into the northern and western parts of the Ofuku pluton as melt lens to form the granite and aplite. The age of the pluton was estimated at 99–97 Ma and 101–98 Ma based on K–Ar dating of hornblende and biotite, respectively. Both ages are consistent within analytical error, indicating that the Ofuku pluton and the associated Yamato mine belong to the Tungsten Province of the San‐yo Belt, which is genetically related to the ilmenite‐series granitoids of the Kanmon to Shunan stages. The aplite contains Cl‐rich apatite and REE‐rich monazite‐(Ce), allanite‐(Ce), xenotime and bastnäsite‐(Ce), indicating that the residual melt was rich in halogens and REEs. The tonalite–granodiorite of the Ofuku pluton contains many three‐phase fluid inclusions, along with daughter minerals such as NaCl and KCl, and vapor/liquid (V/L) volume ratios range from 0.2 to 0.9, suggesting that the fluid was boiling. In contrast, the granite and aplite contain low salinity two‐phase inclusions with low V/L ratios. The granodiorite occupies a large part of the pluton, and the inclusions with various V/L ratios with chloride daughter minerals suggest the boiling fluids might be related to the mineralization. This fluid could have carried base metals such as Cu and Zn, forming Cu ore deposits in and around the Ofuku pluton. The occurrence and composition of fluid inclusions in the igneous rocks from the Akiyoshi Plateau are directly linked to Cu mineralization in the area, demonstrating that fluid inclusions are useful indicators of mineralization. Abstract : The relationship between the magmatism of the Cretaceous Ofuku pluton and mineralization in and around the Akiyoshi Plateau, Yamaguchi Prefecture, Japan was investigated through a combination of field observations, petrographic and geochemical analyses, K–Ar geochronology, and fluid inclusion data. The pluton and the associated mines belong to the Tungsten Province of the San‐yo Belt, which is genetically related to the 101‐97 Ma ilmenite‐series granitoids.